Mapping the Creative Economy Sector in Magelang: Local Synergy Toward Regional Competitiveness - Siti Arifah; Ari Nurul Fatimah; Muhamad Maksum Hidayat; Muhammad Ichwandar Akrianto; Anam Firman Shah; Istikharoh Dwi Prihatiningsih; Alyssa Najmi Nurjanah (Jurnal IPTEK Bagi Masyarakat, 2026)
This study analyzes the spatial distribution, ecosystem dynamics, and development challenges of the creative economy sector in Magelang City using a geospatial approach. GIS, spatial cluster analysis, and the pentahelix framework were employed to examine the relationships among spatial concentration, accessibility, digital transformation, and regional competitiveness. Data were collected from 170 creative economy actors through surveys, interviews, and field observations, while spatial analysis was conducted using ArcGIS 10.8. The results show that creative economy activities are concentrated in several urban clusters, particularly in Potrobangsan, Magelang, and Kramat Utara, supported by better accessibility, infrastructure, and market connectivity. Culinary, craft, and fashion subsectors remain dominant, whereas digital-based subsectors continue to develop more slowly due to limited digital capacity and a less-developed innovation ecosystem. The study also identifies spatial disparities in digitalization, collaboration networks, business performance, and government support across regions. These findings highlight the importance of spatially informed policies, including creative hubs, digital incubation programs, and place-based development strategies, to strengthen sustainable regional competitiveness.